PHOTOGRAPHY AND MEMORY - Moctezuma Moreno, Nayeli Fabiola (Design/Arts/Culture, 2023)
This paper intends to analyze the relationship between memory, aesthetics, and politics in Gustavo Germano Ausencias’s (Absences) series. The text will consist of three parts. In the first section, it is presented a brief journey from photography as a “mirror with memory” to photography as art. The second section reviews the political power of the image during the post-dictatorship. The third section makes a brief analysis of photography as artistic creation and memory builder, as well as its political function, through Gustavo Germano’s photographic essay Ausencias (Absences).